2001
DOI: 10.1029/2000jc900147
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and vertical variability in optical properties of New England shelf waters during late summer and spring

Abstract: Abstract. Relationships between optical and physical properties were examined on the basis of intensive sampling at a site on the New England continental shelf during late summer 1996 and spring 1997. During both seasons, particles were found to be the primary source of temporal and vertical variability in optical properties since light absorption by dissolved material, though significant in magnitude, was relatively constant. Within the particle pool, changes in phytoplankton were responsible for much of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 49 publications
9
49
0
Order By: Relevance
“…levels existed throughout the water column and light level may have had a larger effect on cell size. The presence of larger cells at high light levels in spring surface waters is supported by previous studies using phytoplankton cultures, which have suggested that nutrient-replete cells are generally larger at high light levels than at low light levels (Falkowski et al 1985;Sakshaug et al 1987;Sosik et al 1989). In addition, species differences could have contributed to changes in D with depth.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…levels existed throughout the water column and light level may have had a larger effect on cell size. The presence of larger cells at high light levels in spring surface waters is supported by previous studies using phytoplankton cultures, which have suggested that nutrient-replete cells are generally larger at high light levels than at low light levels (Falkowski et al 1985;Sakshaug et al 1987;Sosik et al 1989). In addition, species differences could have contributed to changes in D with depth.…”
Section: Resultssupporting
confidence: 68%
“…Eukaryotic phytoplankton and Synechococcus decreased in abundance with depth in both seasons ( Table 2). The amplitude of the change was greater in the summer, consistent with a larger change in nutrient availability with depth than in the spring (Sosik et al 2001). Cells increased in size with depth in the summer, in contrast to the spring when cells decreased in size with depth (Table 2).…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations